An effective method for remaining useful life estimation of bearings with elbow point detection and adaptive regression models. (September 2022) - Yan, Mingming; Xie, Liyang; Muhammad, Isyaku; Yang, Xiaoyu; Liu, Yaoyao
Abstract: Bearing is one of the critical components in rotating equipment. Therefore, accurate estimation of the remaining useful life (RUL) of bearings plays a vital role in reducing the costly unplanned maintenance and increasing the reliability of machines. This paper proposes a method for bearing prognostics that uses iteratively updated degradation regression models to capture the degradation trend in bearing's health indicator (HI), and the models are utilized to predict the degradation trajectory of HI and to estimate the RUL of bearings. The importance of determining the time to start prediction by elbow point is explained, which is often overlooked in prognostics. To improve the prognostic performance, an adaptive approach for elbow point detection is designed based on the gradient change of HIs, and a new smooth approach is applied to reduce spurious fluctuations in degradation trajectory. The effectiveness of the proposed method is validated on two publicly available data sets, i.e., IMS and FEMTO bearing prognostics data set, and its prognostic performance is compared with that of three state-of-the-art methods. The obtained results demonstrate that the proposed method can effectively detect elbow point and determine the time to start prediction, and can calibrate the degradation regression model dynamically according to the evolving degradation trend in the HI, which validates its superior prognostic performance. Highlights: A remaining useful life prediction method using the dynamic degradation regression models is proposed. An adaptive approach for elbow point detection based gradient change of health indicator is proposed. The proposed method is tested and validated on IMS and FEMTO bearing data sets, respectively. The proposed algorithm shows superiority comparing to other art-of-the-state methods.